The EU Raw Materials Initiative and effects upon resource-based development: Lessons from Africa - Karin Küblböck (Austrian Foundation for Development Research (ÖFSE), 2013)
In the context of a global surge in demand for commodities, increasing competition and rising prices, several industrialized countries including the European Union have adopted strategies to secure access to raw materials. At the same time, in resource-rich developing countries the debate has intensified about too little benefits from their mineral wealth and about a necessary greater contribution of the mining sector to economic transformation. Through Article 208 of the Lisbon Treaty the EU has a legal obligation to consider the interests of developing countries in all its policies. The question therefore arises if the policies outlined and implemented in the EU Raw Materials Initiative (RMI) live up to this obligation. This Policy Note first outlines the content and implementation of the EU RMI and second assesses its possible effects on policy space in African countries that aim to pursue resource-based development strategies.
Keywords: 330; Erschöpfbare Ressourcen; Internationale Rohstoffpolitik; EU-Staaten; Rohstoffreichtum; Entwicklungspolitik; Afrika